Differentiation of feline coronavirus type I and II infections by virus neutralization test - Shiba, Nozomi; Maeda, Ken; Kato, Hirotomo; Mochizuki, Masami; Iwata, Hiroyuki (Veterinary microbiology, 2007)
Feline coronavirus (FCoV) is divided into two types I and II, based on their growth in vitro and antigenicity. In this study, virus neutralization (VN) test was applied for type differentiation of FCoV infections. Sera of cats which were clinically and serologically diagnosed as feline infectious peritonitis (FIP) possessed significantly higher VN titers to type I FCoV, and sera from cats experimentally infected with FIPV type II had high VN titers to type II but not type I viruses. A total of 79 cat sera collected in the years between 2004 and 2005 were examined to evaluate seroprevalence by the VN test, showing the following results: (1) 50 cats (63.3%) were sero-positive to FCoV; (2) of the 50 FCoV positive cat serum samples, 49 (98%) showed significantly higher titers to type I virus and only one (2%) for type II virus. These results indicate that the VN test described here can be used for serological differentiation of FCoV infections of cats, and that FCoV type I is a dominant type in recent years of Japan.